Pengaruh Likuiditas Dan Profitabiltas Terhadap Perspektif Kesehatan Keuangan Internal Perusahaan (Studi Kasus Pada PT Garuda Indonesia, Tbk 2017 – 2020) - Nijar Kurnia Romdoni Nijar (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
This study aims to determine : (1) The impact of liquidity to company’s internal financial health perspective; 2) The impact of profitability to company’s internal financial health perspective; and 3) The impact of liquidity and profitability to company’s internal financial health perspective. This research is quantitative research by using secondary data which collected from official website of PT. Garuda Indonesia, Tbk and official website of indonesian stock exchange. The research tool in this study is SPSS v.25. The results showed that: 1) Liquidity has no effect to company’ss internal financial health perspective; 2) Profitability has a negative and significant effect to company’ss internal financial health perspective; and 3) Liquidity and profitability simultaneously have a sifnificant effect to company’s internal financial health perspective..